Distribution and interaction of the suitable areas of Beauveria bassiana and Bactrocera dorsalis (Hendel) - Wang, Aqiang; Peng, Sihua; Lian, Yuyang; Yang, Xiaofeng; Jia, Jingjing; Li, Jinlei; Yang, Shuyan; Zheng, Rongjiao; Zhou, Shihao (Frontiers in Ecology and Evolution, 2022)
Climate is a key factor affecting the potential distribution of insects, and the host is another important constraint for the distribution of pests. To elucidate changes in the potential distribution of Beauveria bassiana under climate change scenarios, this paper used the data of two different greenhouse gas (GHG) emission scenarios (RCP2.6, RCP8.5) to predict the potential distribution of B. bassiana and its typical host, Bactrocera dorsalis (Hendel), based on the MaxEnt model. Then, the potential distribution of B. bassiana and B. dorsalis (Hendel) was compared, and their suitable growth area's change and expansion trend under two different GHG emission scenarios were mastered. The results of this study show that the potential distribution area of B. bassiana will increase by 2050 under the RCP8.5 climate scenario, mainly in central Europe and southwestern Asia, with an increased area of 3.28×105 km2. However, under the climate scenario of RCP2.6, the potential distribution area for B. bassiana decreased by 2.0×105 km2, mainly in North America. This study will provide a theoretical basis for the control of B. dorsalis (Hendel) with B. bassiana.